Tinjauan Terhadap Perencanaan Phytomining sebagai Alternatif Tambang Emas Ramah Lingkungan - Di Ajeng Arum Kusuma; Haeruddin Haeruddin (Jurnal Teknologi Sumberdaya Mineral, 2022)
The community's negative paradigm regarding mining activities is still circulating today. They assume that mining only brings harm to the surrounding environment. The community is worried that the mining activities carried out can damage the environment and make them lose their livelihood as farmers. Gold mining can not only be done by conventional methods, but also by the Phytomining method. Phytomining is the production of metal plants by growing plants that can accumulate metals in high concentrations. Phytomining is an environmentally friendly method because in the process it does not use chemical substances that can harm the environment and the surrounding community. In this study, mining planning is carried out which includes prospecting activities, exploration, feasibility studies (feasibility studies) equipped with Environmental Impact Analysis (AMDAL), mining preparation and construction of mining infrastructure, Occupational Health and Safety (K3), management and environmental monitoring. The Phytomining method used can be an alternative solution for environmentally friendly mining activities. In addition, the community will not lose their jobs and earn more because of mining activities. Mining with the Phytomining method has been widely applied in other countries, for that this method also has the potential to be developed in Indonesia.